Immunogenicity of Three Different Influenza Vaccines against Homologous and Heterologous Strains in Nursing Home Elderly Residents. (29th March 2010) - Baldo, Vincenzo; Baldovin, Tatjana; Pellegrini, Michele; Angiolelli, Gabriele; Majori, Silvia; Floreani, Annarosa; Busana, Marta Cecilia; Bertoncello, Chiara; Trivello, Renzo
Abstract : We studied whether MF59-adjuvanted influenza vaccine improves immunity against drifted influenza strains in institutionalised elderly with underling chronic health conditions. Sera from a randomized study, comparing MF59-adjuvanted (Sub/MF59, n = 72 ), virosomal (SVV, n = 39 ), and split (n = 88 ) vaccines, were retested using a hemagglutination inhibition (HI) assay against homologous (Northern Hemisphere [NH] 1998/99) and drifted (NH 2006/07) strains. Corrected postvaccination HI antibody titres were significantly higher with Sub/MF59 than SVV for all strains; GMTs against homologous A/H3N2 and B and both drifted A strains were significantly higher for Sub/MF59 than split. Seroprotection rates and mean-fold titer increases were generally higher with Sub/MF59 for all A influenza strains. MF59-adjuvanted influenza vaccine induced greater and broader immune responses in elderly people with chronic conditions, than conventional virosomal and split vaccines, particularly for A/H1 and A/H3 strains, potentially giving clinical benefit in seasons where antigenic mismatch occurs.